Evaluation of Er:YAG and Er,Cr:YSGG lasers on intraradicular bonding using modified glass fiber tips - Sippus JH; Stape Thiago Henrique Scarabello; Tezvergil-Mutluay Arzu (Japan, 2025)
The aim of this study was to determine whether erbium laser irradiation emitted by modified glass-fiber tips would improve the intraradicular bonding of fiber posts. Forty human canines were endodontically treated and prepared for fiber-post placement. Roots were divided into five groups (n=8); according to the laser-tip combinations (2,940 nm Er:YAG and 2,780 nm Er,Cr:YSGG). Non-irradiated root canals served as control. Posts were cemented with self-adhesive resin cement and subjected to push-out test. Failure modes were characterized, and intraradicular bonded interfaces were analyzed by SEM and submitted to nanoleakage evaluation. Data were analyzed by two-way ANOVA and Tukey test (α=0.05). No significant differences were observed in cervical and middle sections (p>0.05), while significantly higher bond strengths were observed in apical sections (p<0.05). Laser irradiation reduced adhesive failures, cement-dentin gap formation, and nanoleakage apically. Laser-irradiation protocols employing end- or radial-firing tips improved bonding to apical intraradicular dentin contributing to more uniform bonded interfaces.